KONSEP PENDIDIKAN KARAKTER DALAM PENGEMBANGAN MASYARAKAT ISLAM (STUDI PEMIKIRAN BURHANUDDIN AL-ZARNUJI) - Rahmat Hidayat (IAIN Batusangkar, 2019)
A basic implementation of value in education is character. Growing the style and distinctive characteristic is not a job in reversing the palm. However, various processes and stages are done as an effort to achieve this. Burhanuddin Al Zarnuji is a reformer philosopher and provides a theoretical contribution in the world of Muslim renewal and Western . His opinion was expressed as a form of servitude to God for all the opportunities given to humans during his lifetime. Character education is a very much needed concept in today's world. Deterioration and slump morality in the joints of life has resulted in social phenomenology being a special concern from various groups of ordinary people to the elite. Deterioration of character caused by the nature of jumawa over scientific knowledge without propped up there is still the sky above the sky resulting in awareness of living together being blurred. Then the concept of building character is an awareness of how character is an interpretation of ahlakulkarimah in every human life. Society, practitioners and governments are a very similar pattern as an effort to run a concept of character education integration in a theoretical level. It is conceptualized in Zarnuji with several discussions; a). Understanding the science of Fiqh and its importance, b). Intention when studying, c). Choose a science, teacher, friend, and about fortitude, d). Respect for science and scholars, e). Diligent, continuity, and interest, f). Beginning, size and discipline of learning, g). tawakal, h). Fruit revenue from science, i). Compassion and advice, j). Benefit, k). When learning, l). Causes to memorize and forget, m). A good fortune and a fortune barrier, and lengthening and deduction of knowledge. The simplified into three concepts namely; 1). The division on knowledge, 2). The purpose of learning, and 3). Method of study.